Implementasi Gaya Komunikasi Kepemimpinan Pengurus LSBS Unisba dalam Memotivasi Berkesenian - Ayuni Raina Noviane; Ani Yuningsih (Bandung Conference Series: Public Relations, 2024)
Abstract. In the world of leadership, communication has a very important role. A leader's communication style can have a direct effect on the motivation and performance of organizational members. One organization that stands out in the development of artistic interests and talents in the campus environment is LSBS Islamic University Bandung. This organization has a focus on preserving artistic culture, especially Sundanese art. This research uses a qualitative method with a case study approach. The result of this research is the Leadership Communication Style Model in motivating members in art. Abstrak. Dalam dunia kepemimpinan, komunikasi memiliki peran yang sangat penting. Gaya komunikasi seorang pemimpin dapat memberikan efek langsung pada motivasi dan kinerja anggota organisasi. Salah satu organisasi yang menonjol dalam pengembangan minat dan bakat seni di lingkungan kampus adalah LSBS Universitas Islam Bandung. Organisasi ini memiliki fokus pada pelestarian budaya seni, khususnya kesenian Sunda. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Hasil penelitian ini adalah Model Gaya Komunikasi Kepemimpinan dalam memotivasi anggota dalam berkesenian.